The Role of Particles in Command, Question, and Emphasis in Makasae - Antonio Constantino Soares; Noviyanti (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study explores the syntactic and pragmatic roles of particles in the Makasae language, focusing on sentence-final particles such as “di,” “ara,” “gau,” “apa,” and “tai.” Using a qualitative descriptive approach, data was collected through semi-structured interviews and elicitation tasks with native speakers. The data analysis utilized descriptive, pragmatic, and comparative methods to examine how these particles contribute to sentence meaning, particularly in terms of commanding, questioning, emphasizing, and negating actions. The findings reveal that